Epidemiological determinants of aging - Jovanović, Aleksa; Marić, Gorica; Pekmezović, Tatjana (Medicinski podmladak, 2024)
Epidemiology of aging is a dynamic field that has been intensively developing in recent decades. In addition to the increase in the survival rates achieved in people over 65 years, the epidemiological determinants of aging include the accumulation of chronic health problems, the accumulation of exposure to environmental risk factors and endogenous factors, all of which interact with the biological response of the organism, which in old age has its own specificities. Demographic trends at the global level are such that every country in the world records an increase in population and an increase in the proportion of elderly people in the total population. The decrease in mortality in the elderly population has led to an increase in life expectancy, but the structure of mortality in this population group has also changed significantly. The population older than 70 years, on a global level, most often dies from cardiovascular diseases, followed by malignant diseases, respiratory diseases, Alzheimer’s disease and chronic lower respiratory diseases. In modern epidemiology of aging, increasing attention is paid to the concept of biological age (BA) as a significant predictor of health. Traditionally, chronological age (HS) has been used as the primary measure of aging, but increasing research suggests that BS, which takes into account individual variation in the biological processes of aging, may provide a more accurate assessment of risk for various outcomes such as mortality, depression, and different cancers. Terms such as "age-related diseases" or "aging-related diseases" are used for many diseases, however, their usage is not consistent. The term "aging-related diseases" should be used for diseases whose frequency continues to increase with aging and which, therefore, are probably related to this process. On the other hand, the term "age-related diseases" could be used in cases of diseases that have the highest incidence at a certain age.